Expert SQL server 2005 integration services - Knight, Brian, 1976- (Wrox expert one-on-one., 2007)
"As a practical guide for Integration Services ETL development, this book shows you ways to implement your ETL solution requirements from the data to the administration and everything in-between. Each chapter begins with a review of pertinent ETL concepts and moves into working those out into a design with multiple examples and related Integration Services features with the end goal of putting it all together to get a solution"--Resource description page